MEDIA PEMBELAJARAN PENGENALAN HEWAN PURBA BERBASIS AUGMENTED REALITY - Adil Sayidil Waro; Ikrimach Ikrimach (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2024)
Learning media that are often used using printed media such as books or magazines can make the images in them increasingly unclear. By utilizing augmented reality technology, researchers created learning media so that students can find out the origins and forms of ancient animals that can be seen in the images. details by combining the virtual world with the real world and it is hoped that it will make it easier for students to learn and recognize types of ancient animals. This augmented reality-based learning media application for recognizing ancient animals was built using Unity 3D and Vuforia tools. And the augmented reality-based animal learning recognition media application was tested using Blackbox with the results passing the system functional test.